Buestanmyia chiriboga gen. nov. et sp. nov. (Diptera: Tabanidae: Diachlorini) from the Ecuadorian Andes - González, Christian R. (Zootaxa, 2021)
Buestanmyia gen. nov., is described from Pichincha Province, Ecuador with one included species, with B. chiriboga sp. nov. It is characterized by very short and scarce ommatrichia, frons wide and slightly divergent below, basal callus subquadrate with median dorsal projection reaching half the height of the frons, ocellar triangle and ocelli absent, scape 3.5x the length of the pedicel, scape and pedicel with strong and erect hairs, proboscis less than the length of the head, basicosta bare, wings slightly smoky, with clouds on the cells costal and subcostal, vein R4 with a short appendix; cell cup with short appendix.